2010
DOI: 10.1007/s00011-010-0190-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of gastrin-releasing peptide receptor antagonist in carrageenan-induced pleural inflammation in rats

Abstract: The present findings suggest that GRP plays a role in acute inflammation that can be related with the reduction of oxidative damage and that it could be effective in therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…This is in accordance with previous reports of Nmbr agonist-mediated up-regulation of Rela/p65 and Il6 expression in a mouse model of pregnancy in addition to the down-regulatory role of Nmbr antagonists [28]. Increased DNA binding activity of Rela/p65 is regarded as the key step in the onset of labor [18].…”
Section: Zhang Et Alsupporting
confidence: 93%
“…This is in accordance with previous reports of Nmbr agonist-mediated up-regulation of Rela/p65 and Il6 expression in a mouse model of pregnancy in addition to the down-regulatory role of Nmbr antagonists [28]. Increased DNA binding activity of Rela/p65 is regarded as the key step in the onset of labor [18].…”
Section: Zhang Et Alsupporting
confidence: 93%
“…It has been previously shown that GRPR antagonist RC-3095 has antiinflammatory activity in animal models of inflammation (9,10,16). We hypothesized that GRP could have proinflammatory potential, so we tested whether GRP would have a dose-dependent effect on neutrophil recruitment in vivo.…”
Section: Grp Induces Neutrophil Migration In Vivomentioning
confidence: 98%
“…After 1. 5,4,8,16,24,48, and 72 h, animals were killed, cells were cytocentrifuged, stained with Diff-Quick, and counted. cells to migrate toward GRP or leukotriene B 4 (LTB 4 ).…”
Section: Grp Has a Direct Chemoattractant Effect On Neutrophilsmentioning
confidence: 99%
“…Carrageenan-induced pleurisy is a well-characterized experimental model of inflammation, which permits the quantification of exudates and cellular migration (PETRONILHO et al, 2010). The administration of carrageenan into the pleural space leads to pleurisy, characterized by an immediate (TRAP) of V. labrusca extracts (2.5µg mL -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…All efforts were made to minimize animal suffering and to use only the number of animals necessary to produce reliable scientific data. Rats (n=6) were treated intraperitoneally with saline or 10mg kg -1 body wt of V. labrusca extracts 30 minutes before induction of peritonitis through injection of 0.2mL of carrageenan 1% (PETRONILHO et al, 2010). Four hours after inducing inflammation, animals were euthanized, and pleural exudates from each animal were harvested by washing the pleural cavity with 2mL of sterile saline solution for measuring total and differential cell count, lactate dehydrogenase activity (LDH), TNF-alpha levels and total proteins.…”
Section: Methodsmentioning
confidence: 99%